2017
DOI: 10.1002/ep.12593
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the consumption of gasoline in transport sector in pakistan based on ARIMA model

Abstract: An important part of renewable energy strategy of any country is to find suitable transportation fuels to substitute for gasoline and diesel oil. Ethanol has been widely adopted as a substitute for gasoline and diesel oil. The quantity of ethanol required as renewable transport fuel is related to nature of gasoline and diesel demand. Based on data for 1991-2014, this study used autoregressive integrated moving average (ARIMA) method to estimate the consumption of gasoline in transportation sector in Pakistan f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…After we define the mean equation, we analyze volatility dynamics of the daily diesel consumption variable by employing alternative ARCH family models including ARCH, GARCH, EGARCH and TGARCH models 5 . We define the best volatility model by comparing the forecast performances of the models 6 . Table 1 presents the results of the alternative volatility models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After we define the mean equation, we analyze volatility dynamics of the daily diesel consumption variable by employing alternative ARCH family models including ARCH, GARCH, EGARCH and TGARCH models 5 . We define the best volatility model by comparing the forecast performances of the models 6 . Table 1 presents the results of the alternative volatility models.…”
Section: Resultsmentioning
confidence: 99%
“…Their suggestions were followed by Agrawal (2015) who employed an autoregressive distributed lag based co-integration model in order to forecast gasoline and diesel demand for India. In a similar fashion, but with a simpler model, Bhutto et al (2017) forecasted annual gasoline consumption for Pakistan. Given this literature, one research gap is that there are no studies that examine how energy consumption volatility changes in the face of a global pandemic.…”
Section: Introduction Introductionmentioning
confidence: 99%
“…In 1999, government policy was providing incentives for vehicle conversion from oil to CNG. Regardless of this, results from the study show that the share of transport gas is only 2.32%, as Waheed Bhutto et al (2017) indicated that current consumption trend of gasoline depends on its past trends.…”
Section: Discussionmentioning
confidence: 86%
“…It is also used in the field of energy consumption. Bhutto et al estimated gasoline consumption in the Pakistani transport sector in the past ten years by using the ARIMA method [31]. Wang et al used a novel ARIMA model to forecast China's dependency on foreign oil and it will exceed 80% by 2030 [32].…”
Section: Development Of Four Methodsmentioning
confidence: 99%